KOMUNIKASI POLITIK CALON LEGISLATIF PARTAI GOLONGAN KARYA (GOLKAR) DALAM PEMENANGAN PEMILU LEGISLATIF DI KOTA PEKANBARU TAHUN 2014 - Fauzi, Alkindi; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Election is a key element of a democratic country, the election is an event that involves many people, especially the people of Indonesia within a certain area. One of the most important essence of democracy is the institution of political institutions as well as political infrastructure that scope there are political parties as participants, each individual or political party pursued a strategy of trying to compete and to win in the competition and managed to sit in the seat of parliament, especially sitting in the Riau Provincial Parliament legislative seats.This research was conducted in the Office of Pekanbaru DPD Golkar Party, which is addressed in Jl. Sudirman No. 464 Pekanbaru. This research is a descriptive qualitative study using the case study method, in which the case studies used in this study is an intrinsic case study, which is conducted as a case study of the first or the last to want to understand someone. In this study were used as the subject is a person who knows and understands very well regarded by researchers in providing information on the Strategy DPD Golkar Party Pekanbaru in Riau Province Legislative Election 2014 Campaign.From result of analysis Party faction of the party's work in Indonesia are still getting great support darimasyarakat including in the city of Pekanbaru. In the 2014 legislative elections the party faction works kembalimenempatkan candidate as the winner. Factors affecting the Golkar party candidate winning legislative elections supported by Political Cost measurable and produce victory in legislative elections in 2014.Keywords: Political Communication Legislative Candidates